2020
DOI: 10.3390/nu12123723
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in One-Carbon Metabolism in Celiac Disease

Abstract: Celiac disease (CD) is an autoimmune enteropathy associated with alterations of metabolism. Metabolomics studies, although limited, showed changes in choline, choline-derived lipids, and methionine concentrations, which could be ascribed to alterations in one-carbon metabolism. To date, no targeted metabolomics analysis investigating differences in the plasma choline/methionine metabolome of CD subjects are reported. This work is a targeted metabolomic study that analyzes 37 metabolites of the one-carbon metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…Remarkably, differences in methionine, choline, and choline-derived lipids content in CD subjects were described, suggestive of an affectation of one-carbon metabolism. This alteration of methionine metabolism in CD subjects was recently confirmed and extended using a LC-MS/MS approach [17]. In this study, a down-regulation of the trans-sulphuration pathway in CD patients was observed, in particular.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Remarkably, differences in methionine, choline, and choline-derived lipids content in CD subjects were described, suggestive of an affectation of one-carbon metabolism. This alteration of methionine metabolism in CD subjects was recently confirmed and extended using a LC-MS/MS approach [17]. In this study, a down-regulation of the trans-sulphuration pathway in CD patients was observed, in particular.…”
Section: Introductionsupporting
confidence: 76%
“…Effectively, available evidence from metabolomic studies certified the presence of minor but significant differences in the metabolic profile between healthy individuals and celiac patients (children and adults) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In these studies, using NMR or MS-based methods, biological samples from different origins including faecalis material, plasma, serum, and urine were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, targeted metabolomic analysis investigating differences in the plasma choline/methionine metabolome of CD subjects were not reported. Only one study [ 81 ] in 17 children with CD, treated with a GFD, and 17 healthy control siblings has recently demonstrated the persistence of defects in the trans-sulfuration pathway of CD, despite dietary treatment. Conversely, choline metabolism seem to be preserved [ 81 ], a finding that might add further support to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%